The use of computer-mediated tasks in an ESL classroom - Misrah Hamisah, Mohamed; Mohamed Amin, Embi (2014)
The use of ICT especially computer technology match the task based learning framework where students and teachers can benefit from having direct access to real audiences synchronously or asynchronously. This leads to positive perceptions and attitudes towards technology use in language teaching among educators especially in cultivating language tasks in learning and teaching. However, most of the educators are more concern of their own knowledge of the technology use. This has brought so many issues related to the application of computer-mediated tasks among teacher trainees during their teaching practicum. Therefore, this study reports on the implementation of computer-mediated tasks in teaching English as Second Language among teacher trainees pursuing a diploma in TESL from a local university in Malaysia. The quantitative findings showed that majority teacher trainees have positive perceptions towards the implementation of computer-mediated tasks. Ironically, the qualitative findings revealed a contrasting result where more than half of the teacher trainees rarely used computer-mediated tasks in the classroom due to several factors. These factors have given huge implication on the policy makers, schools, lecturers and teacher trainees themselves. The findings finally point to the need for future studies on the level of teacher trainees‟ exposure to computer-mediated tasks.